Uncovering Hidden Fiduciaries in South Korean Private Law - Ying Chieh Wu (Contemporary Social Sciences, 2022)
This article attempts to extend the list of fiduciary relationship by unlocking some of the hidden fiduciaries in other areas of South Korean private law. The reason for this is as follows. The exact label of “fiduciary relationship” may not be widely used, but the underlying mechanisms can be found in many other legal relationships under South Korean private law. Through the clarification of the types of fiduciary relationship, even though it may not be complete, we can come to understand when the fiduciary duty (or the duty of loyalty) and remedies for its breach should be applied. This article shows us that the following should be considered to be fiduciary relationships in addition to trustees and company directors: agents, mandataries, parents and adult guardians, executors of inheritance, commission agents, and partners. It must be stressed that the list is not yet closed. There is always the possibility for a new candidate being added to the list. Like cases must be treated alike, for certainty, systematic consistency, and legal stability are vital for any legal system.